The jaundiced newborn: which early monitoring for a safe discharge? - S. Pratesi; C. Dani (PAGEPress Publications, 2013)
Neonatal jaundice is one of the most common causes of prolonged hospital stay or readmission of a near-term or term baby. Reason of concern at early discharge of a jaundiced newborn is that of bilirubin neurotoxicity, even if a serum bilirubin concentration surely toxic for the brain is still unknown. Kernicterus and severe neonatal hyperbilirubinemia are still problems in the third millennium and the American Academy of Pediatrics claimed the pediatric community to increase vigilance in order to reduce the occurrence of these dramatic events. The only existing kernicterus registry is the pilot USA kernicterus registry whose data on 125 kernicteric term and near term babies from 1992 to 2004 have been recently published. Nobody of the kenicteric babies into the USA register had a serum bilirubin levels below 20 mg/dL. All the babies who suffered from kernicteric sequelae were discharged as healthy from hospital and then, 86% of them, readmitted in the first ten days of life. In the majority of babies (69%) a cause of the severe hyperbilirubinemia was not found. Current knowledge on mechanism of neurological damage induced by bilirubin, unfortunately, does not allow to have a universal evidenced based guideline on how to manage neonatal jaundice. Thus, the existing national guidelines contain inevitable differences in the recommended procedure. Waiting for the future italian guidelines the paper illustrates a proposal of management of neonatal jaundice in term or near term newborns based on available scientific evidence and national guidelines published in english language.